GC-MS, Phytochemical Analysis and In Silico Approaches of a Medicinal Plant Acalypha indica (Journal of Scientific Research, 2022)
The goal of this study is to look into the preliminary phytochemical and GC-MS analyses of a methanol extract of the leaves of Acalypha indica. Alkaloids, tannins, steroids, saponins, flavonoids, glycosides, and phenolic substances are found in leaf extract after phytochemical analysis. A. indica is a plant that grows in the southern Indian state of Tamil Nadu. It has medicinal characteristics and is used as a diuretic, anthelmintic, and respiratory disorders like bronchitis, asthma, and pneumonia. The present work is designed to investigate GC-MS. Thirty compounds are found in the leaf extract. The structure-based biological activities study supported the Pass online database findings from the current study support that the use of this plant compound responsible for the anticancer activity is based on structure-based drug development. Based on in-silico results, it was shown that the interactions of hydrogen bonds, binding affinity with JAK2 kinase inhibitors, tumor suppressor proteins pRB Retinoblastoma protein, and COX-2 target proteins were compared with known values. It can be considered an increase in the possibility of conniving potential anticancer drugs as an anti-inflammatory agent.